Modelling academic help-seeking behavior among low academic achieving students in a Malaysian private university - Omar, Mariani (2017)
Modelling academic help-seeking behaviour is the essential forming factors that may influence academic success. However, in the context of academic help-seeking behaviour, there are many factors which influenced students’ lowachieving. The purpose of the study examined the correlation between the predictor variables of social support, self-concealment, spiritual well-being and mediator variables of psychological distress, help-seeking attitude, and moderator variable of gender, with criterion variable of academic help-seeking behaviour, was constructed. The study utilized the Cramer model of helpseeking as a theoretical model in providing a significant basis for explaining and predicting academic help-seeking behaviour among low achievement University of Kuala Lumpur’s (UniKL) students. Four hundred students aged between 18 to 24 years from four institutions of UniKL were included in the samples. Stratified random sampling methods are used to select samples in the study. This quantitative study uses correlation design. Respondents answered the questionnaires of Social Supports Scale (Zimet, Dahlem, Zimet & Farley, 1988), Self-Concealment Scale (Larson & Chastain, 1990), Spiritual Well-Being Scale (SWBS) by Paloutzian and Ellison (1982), Kessler’s Psychological Distress Scale (K10; Kessler & Mroczek, 1994), and Help-seeking Attitude scale (Fischer & Farina, 1995). Results of the study of the structural equation modelling indicated that low achieving UniKL’s students have lower level academic help-seeking behaviour. Spiritual well-being was the strongest predictor of academic help-seeking among low achievement UniKL’s students. This academic help-seeking behaviour is influenced by spiritual well-being which has been cultivated among students. Conversely, psychological distress and help seeking attitude mediate the effect of academic help-seeking behaviour on social support and self-concealment, especially among low achievement UniKL’s students. The findings of the study proposed that social support, self-concealment, spiritual well-being, psychological distress, and help-seeking attitude were valuable and explained 75% of the variance in academic help seeking behaviour. The findings of the study also showed the standardized beta coefficients for all dot, not equal zero when regression against low academic achievement students. The study concluded that the implication on the importance of spiritual well-being and spiritual well-being as a highly influencing factor towards academic help-seeking behaviour.